Wednesday

November 26, 2014

November 26, 2014

Posted by **DANIELLE** on Wednesday, April 11, 2007 at 11:00pm.

using (a-b)^2

(sqrt3)^2-2(sqrt3)(5) +(sqrt5)^2

=3-2sqrt15+5

=8-2sqrt15

If you were doing (sqr(3) + sqr(5))^2

yes, you are right.

**Answer this Question**

**Related Questions**

Algebra II (check) - Assume that no denominator equals 0. sqrt12 - sqrt18 + ...

algebra - what is the perimeter of a square with sides that are sqrt3 + sqrt5 on...

Algebra - Find the exact solution(s) of the system: x^2/4-y^2=1 and x=y^2+1 A)(4...

Math - Find the exact solution(s) of the system: x^2/4-y^2=1 and x=y^2+1 A)(4,...

ALGEBRA 1 - change 50 to 25*2 sqrt 50 = 5 sqrt2 change 8 to 4*2 Nope: (sqrt3-...

math b - Combine the radicals sqrt 72 + sqrt 18 6sqrt7 - 4sqrt7 Multiply & ...

Algebra - Find a polynomial function of degree 3 with the given numbers as zeros...

Math - Find the quotient function f/g for f(x)=sqr(x+1) and g(x)= sqr( x-1). My...

Math - Find the quotient function f/g for f(x)=sqr(x+1) and g(x)= sqr( x-1). My ...

algebra - simplify: 6sqrt7-sqrt7 A. 6 sqrt7 B. 5 sqrt 7 C. 5 D. 6 Simplify: ...